Obstructive Sleep Apnea Treatment with Epap Nasal Devices: Physiological Principles and Limitations - Hakim T.S.; Camporesi E.M. (Journal of Sleep And Sleep Disorder Research, 2017)
Expiratory Positive airway pressure (EPAP) devices such as prevent have been used for treatment of obstructive sleep apnea without discussing their limitations. In this short review we discuss the physiological limitations of EPAP devices during inspiration and during expiration. During spontaneous breathing, when EPAP is excessive, the patient would have difficulty breathing in because lung compliance decreases at higher volumes. Furthermore excessive EPAP could lead to progressive trapping of air in the lungs. An ideal EPAP device should allow the patient to adjust the resistance to a comfortable level that would provide EPAP without a progressive buildup in pressure, without compromising tidal volume, without causing CO2 retention, and without disturbing sleep. The use of EPAP devices with adjustable resistance is essential for best results in treatment of obstructive sleep apnea and snoring.
Keywords: obstructive sleep apnea